The Financial Diagnostics Based on Static and Dynamic Indicators at the Level of Cash and Carry Type of Entity - Bogdan Cosmin GOMOI (CECCAR Business Review, 2023)

(untitled)
The management activity is characterized by complexity, dynamism and volatility. An extremely important coordinate in taking the best decisions for the company is the relevant management of the financial-accounting information. In this respect, the financial diagnostics is used, so as to identify the strengths, for perpetuating them, and the weaknesses, so as to find solutions for their improvement. The article hereby aims to perform a financial diagnosis over a period composed of seven consecutive financial years, 2015-2021 respectively, at the level of a company with seniority and experience on the Romanian market, Metro Cash and Carry România.